2019
DOI: 10.1016/j.displa.2019.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Plug and play perimetry: Evaluating the use of a self-calibrating digital display for screen-based threshold perimetry

Abstract: This study evaluated the feasibility of using a 'self-calibrating' display (EIZO CG277) to perform screenbased threshold perimetry. Such displays incorporate their own integrated photometer, so could potentially be used 'straight out of the box', without the need for time-consuming and costly luminance calibration by skilled experts. Concerns remain, however, due to the fact that the internal calibration of such devices is imperfect (i.e., is limited to a single screen location only) and due to lingering doubt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…However, we have demonstrated subsequently that measurements from this inbuilt photometer can be substituted for a formal photometric calibration, without any appreciable loss of accuracy or reliability in visual field measurements. 58 Furthermore, we have made the necessary Matlab code for controlling the photometer available online ( https://github.com/petejonze/myEIZOSensor ), allowing calibration to be performed automatically (e.g., overnight or before the first test of each day). Finally, we have also shown that this monitor (which comes with a factory-calibrated certificate of uniformity) remains photometrically stable over its spatial extent for at least 20 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we have demonstrated subsequently that measurements from this inbuilt photometer can be substituted for a formal photometric calibration, without any appreciable loss of accuracy or reliability in visual field measurements. 58 Furthermore, we have made the necessary Matlab code for controlling the photometer available online ( https://github.com/petejonze/myEIZOSensor ), allowing calibration to be performed automatically (e.g., overnight or before the first test of each day). Finally, we have also shown that this monitor (which comes with a factory-calibrated certificate of uniformity) remains photometrically stable over its spatial extent for at least 20 months.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we have also shown that this monitor (which comes with a factory-calibrated certificate of uniformity) remains photometrically stable over its spatial extent for at least 20 months. 58 Taken together, this makes the prospect of a simple plug-and-play perimeter—one that combines open source software with ordinary, commercially available hardware—a genuine, pragmatic possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Visual specialists could provide visual tests but also the characterized devices to ensure correct performance of the patient. Future solutions could involve the development of hardware with integrated photometers for self-calibrating, [35] but the cost is still high, and this solution is not affordable in handheld devices.…”
Section: Possible Solutionsmentioning
confidence: 99%
“…It was modified in the present work to more closely mimic conventional static threshold perimetry, most notably by employing a Zippy Estimation by Sequential Testing (ZEST) thresholding algorithm, 15 a central fixation cross, and a button press response. The software was implemented using Psychtoolbox 3, 16 and we used bit stealing to ensure >10-bit luminance precision, 17 with extensive photometric calibration to ensure stimulus uniformity across the display (see Kyu Han and Jones 18 for technical details regarding the calibration method). Unlike conventional perimetry, participants received visual Figure 1.…”
Section: Normally Sighted Adultsmentioning
confidence: 99%